Avaliação ambiental da microbacia do córrego Três Barras como subsídio para elaboração de um prognóstico na área de influência da avenida Parque em Cuiabá - MT - Santos, Adriana Bussiki Figueiredo (2013)
The medium and large cities have in common indexes of urbanization increasingly growing. The city of Cuiabá has 98.1% of its population in urban areas, a factor that supports the disorderly occupations of land and building on its waterproofing processes irregular occupations in public areas and in private areas too. The Watershed of the Stream Três Barras has, as scenario, an environment with low environmental quality, since portions of legal permanent preservation areas are disregarded, such as the abolition of green areas, grounding the banks of the stream, illegal construction of housing, stricken areas of garbage and construction waste, and release of domestic sewage in nature, resulting in distortion of the natural environment, in other words, to exist APP functional by no more owning the hydromorphic soil (Ultisol), present in areas of valley bottom the portion not disturbed. The diagnosis in the area surrounding the stream, representing the stretch that receive influence when deploying Avenue Park, was founded in VERAH method, which has components as Vegetation, Erosion, Residue, Water and Housing, providing data and information that can help in building a prognosis with goals and interventions necessary to the water body and improvement of environmental indexes of the Watershed.